Analisis Karakter Panda sebagai Model Desain pada T-Shirt Electrica Panda Artwear Medan - Iqbal Mudri Khatikno; Raden Burhan SND (Mahesa Research Center, 2020)
The aim of this study is to describe the tendency of colours and techniques as well as design principles of panda character used in Electrica Panda t-shirt. This study was focused on seven fundamental parameters, namely balance, emphasis, rhythm, unity, proportion, technique, and colour. The data was collected using observational, interview, and documentation methods. The data was analysed using descriptive analysis, which describes the balance, emphasis, rhythm, unity, proportion, technique, and colour used in t-shirt design of Electrica Panda Artwear Medan production. The results of the study are; in the design of Electrica Panda Artwear, the balance used was varied; design used was varied; there was different emphasis used in each design; the rhythm used in each design was different; all designs used were harmonious; the proportions applied were varied based on the blueprint; the drawing techniques used were digital technique and followed by a manual Sablon painting process; as well as the colours employed were diverse which leads to a clear meaning of the design.